1999
DOI: 10.1046/j.1365-2842.1999.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of masseter and temporalis EMGs: a comparison of anterior guided versus balanced occlusal concepts in patients wearing complete dentures

Abstract: The lack of easily measurable, objective physiological activity parameters of the masseter and temporalis muscle during jaw movements in humans has led to the consideration to revise data of surface electromyographies (EMGs) by applying a computerized quantification method. The aim of this follow-up analysis was to get quantitative data out of EMG-records of an earlier study. These records were obtained with two different splints, splint 1 providing an anterior front-canine guidance and splint 2 providing bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 7 publications
1
34
0
8
Order By: Relevance
“…These demarcations served as an idea to develop diagnostic methods for bruxism 8 . Bruxchecker is a simple and effective device that is used for determining the patterns of occlusal contacts performed at lateral grinding movements of the lower jaw performed by patients with bruxism and is used to diagnose this condition 9 . Using the bruxchecker, we can record the occlusal contact points and direction of grinding during nocturnal bruxism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These demarcations served as an idea to develop diagnostic methods for bruxism 8 . Bruxchecker is a simple and effective device that is used for determining the patterns of occlusal contacts performed at lateral grinding movements of the lower jaw performed by patients with bruxism and is used to diagnose this condition 9 . Using the bruxchecker, we can record the occlusal contact points and direction of grinding during nocturnal bruxism.…”
Section: Methodsmentioning
confidence: 99%
“…Bruxchecker (bruksoanalizator) predstavlјa jednostavnu i efektivnu spravu koja se koristi pri određivanju okluzalnih šema kontakata koje se izvode pri lateralnim kretnjama donje vilice i koje prave pacijenti sa bruksizmom, a služe za dijagnostikovanje bruksizma 8 . Pomoću bruksoanalizatora mogu da se evidentiraju okluzalne kontaktne tačke za vreme noćnog bruksizma 9 . Bruksoanalizator može isto tako da se koristi i kao indikator korelacije između stanja okluzije i pojave parodontalne bolesti i TMD-a 10 .…”
Section: Materijali I Metodeunclassified
“…Because it was clear that tremendous occlusal forces were exerted by parafunctional bruxism activity, which very much depends upon the occlusion schemes [26][27][28][29], contemporary concepts of occlusion slowly shifted to concepts based on the parafunctions of masticatory organ, grinding and clenching [30]. Therefore, it must be considered that these loads contribute to many oral diseases [31,32]; that is, excessive loads cause periodontal breakdown in some cases, and hard tissue breakdown or temporomandibular disorders in other cases.…”
Section: Bruxism and Oral Diseasementioning
confidence: 99%
“…It has been reported that occlusions with anterior canine guidance allow less muscular activity and forces within the stomatognathic system during parafunction than occlusions with group function patterns and balanced occlusions [10][11][12][13][14][15][16][17][18][19]. For long-term success and stability it has been suggested that an occlusal concept be established which keeps the muscular activity of the patient at the lowest level and thereby prevents the stomatognathic system from dysfunction or possibly self-destruction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For long-term success and stability it has been suggested that an occlusal concept be established which keeps the muscular activity of the patient at the lowest level and thereby prevents the stomatognathic system from dysfunction or possibly self-destruction [20,21]. These references suggest that this is best accomplished by an anterior protected articulation (mutually protected articulation; [2]), even for complete dentures [15,[22][23][24][25]. These studies suggest that it would be worthwhile to reevaluate previously accepted occlusal rules in order to establish whether occlusion with anterior protected articulation is the occlusal scheme of choice.…”
Section: Introductionmentioning
confidence: 99%